PENGARUH PROGRAM BILINGUAL DALAM MENINGKATAN PRESTASI BAHASA SANTRI DI PONDOK PESANTREN.MAMBAUL ULUM BATA-BATA PANAAN PALENGAAN PAMEKASAN - Moh Mujib; Abd Majid (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
The bilingual program is a structural design, design with the aim of making it easier to learn two languages, namely Arabic and English. Therefore, as educators and teachers in carrying out their duties and functions, they must have teacher competencies and standards. This research aims; First, to describe the bilingual program in improving students' language achievement at the Bata-Bata bilingual center. Secondly, to find out and describe the effect of the bilingual program in improving the language achievement of students at the Bata-Bata bilingual center. This research method is quantitative with a population of 50 students and a sample of 50 students taken using a layered sampling technique (Stratified Random Sampling). Methods of data collection in the form of questionnaires, interviews, observations, and documentation. The data analysis used simple regression analysis. The results of this study show 1). The bilingual program in improving language achievement is in the sufficient category. This is evidenced by the largest percentage of 64% for the bilingual program and 60% for the achievement of students. These findings are then supported by observation data and interviews conducted by the author. 2). There is a positive and significant influence between bilingual programs in improving the language achievement of students at Bata-Bata bilingual center of Mambaul Ulum Bata-Bata Panaan Boarding School, Palengaan, Pamekasan while the magnitude of the influence is 23.1%, the remaining 76.9% is influenced by other factors.Keywords: Influence of Bilingual Program, Student's Language Achievement. Program bilingual suatu rancangan struktur, desain, dengan tujuan mempermudah untuk belajar dua bahasa yaitu bahasa arab dan bahasa ingris, Oleh karena itu sebagai tenaga pendidik dan guru dalam menjalankan tugas dan fungsinya harus memiliki kompetensi dan standar guru.Penelitian ini bertujian; Pertama, untuk mendeskripsikan progam bilingual dalam meningkatkan prestasi Bahasa santri di Bata-Bata bilingual centre Pondok Pesantren Mambaul Ulum Bata-Bata Panaan, Palengaan, Pamekasan. Dan yang kedua, untuk mengetahui dan mendiskripsikan Pengaruh progam bilingual dalam meningkatkan prestasi Bahasa santri di Bata-Bata bilingual centre Pondok Pesantren Mambaul Ulum Bata-Bata Panaan, Palengaan, Pamekasan Metode penelitian ini bersifat kuantitatif dengan Populasi sebanyak 50 siswa dan sampel sebanyak 50 siswa yang diambil menggunakan teknik penarikan sampel terlapis (Stratified Random Sampling). Metode pengumpulan data berupa angket, wawancara, observasi, dan dokumentasi. Adapun analisis data menggunakan analisi regresi sederhana. Hasil penelitian ini menunjukkan 1). Progam bilingaul dalam meningkatkan prestasi bahasa berada dalam kategori cukup, Hal ini debuktikan dengan persentase terbesar 64% untuk progam bilingaul dan 60% prestasi santri. Hasil temuan ini kemudian didukung oleh data observasi dan interview yang dilakukan penulis. 2). Ada pengaruh yang positif dan signifikan antara progam bilingual dalam meningkatkan prestasi bahasa santri di Bata-Bata bilingual centre Pondok Pesantren Mambaul Ulum Bata-Bata Panaan, Palengaan, Pamekasan adapun besarnya pengaruh tersebut sebesar 23,1%, sisanya 76,9% dipengaruhi oleh faktor lain.Kata Kunci : Pengaruh Program Bilingual, Prestasi bahasa Santri